Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13018-018-0981-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of collum femoris-preserving stems and ribbed stems in primary total hip arthroplasty

Abstract: BackgroundThis retrospective study investigated the relative benefits of using a collum femoris-preserving prosthesis or ribbed stem during total hip arthroplasty (THA).MethodsThe clinical results were compared of patients who underwent THA, between January 2010 and December 2012, with either a CFP prosthesis or a ribbed stem (66 and 75 patients, respectively, aged 43.4 ± 10.8 and 42.3 ± 9.8 years). Patients were assessed using the Harris Hip Score (HHS), Western Ontario and McMaster University Osteoarthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(20 reference statements)
0
2
1
Order By: Relevance
“…It is widely believed that difference of more than 15 mm can lead to gait disorders, lower back pain, and general dissatisfaction [40]. However, some studies reported that differences in leg length was not associated with the feelings of patients [41]. Compared with before the operation in the current study, the length of the lower limbs increased in both groups, due to the replacement of the collapsed femoral head by the prosthetic femoral head.…”
Section: Discussioncontrasting
confidence: 45%
“…It is widely believed that difference of more than 15 mm can lead to gait disorders, lower back pain, and general dissatisfaction [40]. However, some studies reported that differences in leg length was not associated with the feelings of patients [41]. Compared with before the operation in the current study, the length of the lower limbs increased in both groups, due to the replacement of the collapsed femoral head by the prosthetic femoral head.…”
Section: Discussioncontrasting
confidence: 45%
“…In this case, the distal-lateral part of the stem is tightly flattened on the lateral femur, and an aggressive compression force might cause PFF. [23,24] Thus, our suggestion is that surgeons should pay additional attention during the operation to sufficiently preserve the femoral neck length and evaluate the patients’ femoral neck-preserving ratio preoperatively to help reduce the possibility of PFF (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…8 However, another study comparing the CFP stem with the ribbed stem demonstrated that the CFP stem was more likely to cause an increase in the leg length and the occurrence of periprosthetic fractures. 9 Klein et al 10 showed that both the CFP stem and the Corail stem (DePuy Orthopaedics, Warsaw, IN, USA) had similar hip function scores, but they did not evaluate the FO or leg length. Thus, whether femoral neck-preserving hip prostheses perform better than traditional neck implants that require resection remains unclear.…”
Section: Introductionmentioning
confidence: 99%